Synthesis and photocatalytic activity of BiVO4, Ag-BiVO4 and Cu-BiVO4 in degradation of methylene blue / \c by Jong Chin Yun - Jong, Chin Yun (2013)
In the past few decades, water contamination has been pointed out as one of the serious problem of modern society due to rapid growth of industrialization. Bismuth vanadate (BiVO4) is a promising photocatalyst that works well in removing this highly coloured wastewater under visible light irradiation. Therefore, this study has focused on the synthesis and modification of BiVO4 as well as their photocatalytic activities in degrading the methylene blue dye solution. BiVO4 photocatalysts were successfully synthesized by solution combustion method using two different bismuth precursors (bismuth nitrate and bismuth acetate), ammonium metavanadate and citric acid. A series of combustion temperature (500 – 700 °C) was used during BiVO4 preparation step. Effects ofbismuth precursor and combustion temperature on the properties of BiVO4 were studied. The BiVO4 formed were in monoclinic structure with nearly spherical shape. Acetate based BiVO4 series exhibited better physical properties (small particle size and high surface area) than nitrate based BiVO4. Increment in particle size, pore size, crystallinity and reduction in pore volume and surface area of prepared BiVO4 were observed as combustion temperature increasing from 500 to 700 °C. Photocatalytic efficiency of BiVO4 was found strongly influenced by its crystallinity and surface area. BiVO4 (N600) possessed the highest photocatalytic activity with degradation rate, 3.4 x 10-2 ppm/min was chosen to be modified with Cu and Ag, respectively. Ag-BiVO4 exhibited higher photocatalytic activity in degradation of MB than Cu-BiVO4. Ag loaded on the BiVO4 was existed in Ag2O form. Improvement in photocatalytic performances was ascribed to the efficient of charge separation in the Ag2O-BiVO4 interface. The optimal Ag loading was 5%, while excess Ag loading inhibited photocatalytic activity. 5% Ag-BiVO4 was chosen as the best photocatalyst in this study and its ability to degrade MB were transpired by its photocatalytic activity in the effect of operational parameters.